Trust evaluation model of social internet of things based on implicit social relationship - Hongbin ZHANG; Fan FAN; Dongmei ZHAO; Bin LIU; Yan YIN; Jian LIU (网络与信息安全学报, 2023)
The social internet of things （SIoT） is a new paradigm that combines social networks and the internet of things to enhance network scalability and navigability.However, with increased openness and mobility of intelligent objects, there are rising security risks related to information security and reliable service delivery, which poses a significant challenge to the SIoT.Trust is a critical factor in providing secure and reliable services.Therefore, a new trust assessment model was proposed from the perspective of social relationships.A trust transfer algorithm was proposed based on the explicit social relationships and potential features between nodes.The algorithm can tap and establish the implicit social relationships among nodes to solve the SIoT sparsity and cold start problem.Additionally, the social relations were fine-grained and divided to build a single-relationship sub-network.Multiple single-relationship sub-networks were fused to build a multiple-relationship composite network.Thus, the impact of multiple dynamically changing social relationships among nodes on trust evaluation can be effectively fused.The comprehensive trust assessment of intelligent objects was conducted based on three indicators: direct trust, indirect recommendation trust, and service satisfaction.The experimental results on real smart city datasets demonstrate the model’s robustness in non-sparse and sparse network scenarios.It can effectively evaluate trusted and untrusted objects in the network and improve the accuracy and convergence of trust evaluation.